2011
DOI: 10.2169/internalmedicine.50.4437
|View full text |Cite
|
Sign up to set email alerts
|

Established Osteoporosis Associated with High Mortality after Adjustment for Age and Co-Mobidities in Postmenopausal Japanese Women

Abstract: Objective Osteoporosis has been reported to increase the risk of mortality. However, these reports did not evaluate the effects of co-mobidities and the severity of osteoporosis on mortality. The aim of our study was to determine whether or not major osteoporotic fractures contribute to the increased mortality risk in Japanese women. Method We conducted a prospective observational study. Risk factors contributing to mortality were assessed by Cox's proportional hazard model. Subjects A total of 1,429 ambulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The high morbidity and mortality of these diseases can intensify both individual and governmental financial burdens. 2,3 In 2010, in a position statement regarding osteoporosis management in postmenopausal women, The North American Menopause Society reported that weight-bearing exercise, which could be as simple as brisk walking or jogging, was beneficial to bone development and maintenance 4 through mechanical loading of bone. In addition, brisk walking has been one of the most acceptable exercise programs 5 and can be easily incorporated into an individual's current lifestyle.…”
mentioning
confidence: 99%
“…The high morbidity and mortality of these diseases can intensify both individual and governmental financial burdens. 2,3 In 2010, in a position statement regarding osteoporosis management in postmenopausal women, The North American Menopause Society reported that weight-bearing exercise, which could be as simple as brisk walking or jogging, was beneficial to bone development and maintenance 4 through mechanical loading of bone. In addition, brisk walking has been one of the most acceptable exercise programs 5 and can be easily incorporated into an individual's current lifestyle.…”
mentioning
confidence: 99%
“…Increased mortality has been found in osteoporotic patients [7,8]. Further, osteoporotic related vertebral deformities have been reported to increase mortality and fracture [914].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with established osteoporosis have been reported to have a high mortality rate,14,15 and vertebral deformities are known to predict mortality and fracture rate 1621. Anti-osteoporotic therapy has been reported to reduce mortality in those at high risk of fractures 2,22,23…”
Section: Discussionmentioning
confidence: 99%